Pistacia vera: chemical composition and pharmacological activities (Pistachio nuts) - El Bairi K.; Jadda H.; Terkmane C. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The pistachio is a nutrient-dense nut with a heart healthy fatty-acid profile as well as protein, dietary fiber, potassium, magnesium, vitamin K, g-tocopherol, and a number of phytochemicals.this particular composition makes this dry fruit a fabulous way to prevent cardiovascular disease. The details of these pharmacological activities will be discussed in this review of the literature.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)